Pediatric orthopaedics and sport injuries a quick reference guide - Sarwark, John F.; LaBella, Cynthia R. (American Academy of Pediatrics, 2014)
".truly impressed by the expanse of topics and the ease of using this book for daily care. This new addition to orthopedic and sports injury references is welcomed and fills a gap in the literature." Doody's Review of 1st edition